Bartsocas-Papas Syndrome: Unusual Findings in the First Reported Egyptian Family - E. M. Abdalla; H. Morsy (Case Reports in Genetics)
Bartsocas-Papas syndrome (BPS) is an autosomal recessive syndrome with severe craniofacial, limb, and genital abnormalities. As of 2011, 24 published cases and families were registered in the Orphanet Report Series. Compared to other disorders characterized by pterygia, the condition is usually more severe and often lethal: most affected patients die in utero or shortly after birth. We report the first Egyptian family with Bartsocas-Papas syndrome comprising three cases; our proband who was a female infant with severe craniofacial and limb anomalies typical of Bartsocas-Papas syndrome, a similarly affected female fetus which died in utero at the 7th gestational month, and a 16-year-old mentally retarded uncle who presented with some of the typical features of Bartsocas-Papas syndrome, including syndactyly, thumb hypoplasia, and microphthalmia. This male patient actually did not present with pterygia, however, we find his clinical description noteworthy.